2020
DOI: 10.1002/acn3.51163
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration trajectory in pediatric and adult/late DM1: A follow‐up MRI study across a decade

Abstract: Objective: To characterize the progression of brain structural abnormalities in adults with pediatric and adult/late onset DM1, as well as to examine the potential predictive markers of such progression. Methods: 21 DM1 patients (pediatric onset: N = 9; adult/late onset: N = 12) and 18 healthy controls (HC) were assessed longitudinally over 9.17 years through brain MRI. Additionally, patients underwent neuropsychological, genetic, and muscular impairment assessment. Inter-group comparisons of total and voxel-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 42 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…Interestingly, this association was only found at follow-up, when patients differed more from HC in WM damage, suggesting that visuoconstruction abilities could be highly sensitive to changes in WM integrity. Both visuospatial and visuo-construction abilities have previously shown to be a hallmark of the DM1 cognitive pro le 16,31−33 and are reliable predictors of both cognitive and structural brain progressive degeneration 11,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this association was only found at follow-up, when patients differed more from HC in WM damage, suggesting that visuoconstruction abilities could be highly sensitive to changes in WM integrity. Both visuospatial and visuo-construction abilities have previously shown to be a hallmark of the DM1 cognitive pro le 16,31−33 and are reliable predictors of both cognitive and structural brain progressive degeneration 11,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Although still a matter of debate, there is a neurodegenerative hypothesis concerning the progression of the disease, supported by neuropathological, neuropsychological and neuroimaging evidence [8][9][10][11][12][13] . However, longitudinal studies assessing precise neurodegenerative patterns are scarce, and very few have assessed WM variations over time 11,14−16 .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of neurodegenerative pathological features, including NFTs, LBs and WM abnormalities, as well as a progressive cognitive decline reported by a limited number of longitudinal studies have been found in DM1 patients, which support that DM1 is in part a neurodegenerative process. However, another view supports that the progressive CNS dysfunction may be responsible for cognitive impairment, rather than neurodegenerative changes, since the distinct brain alteration patterns different from neurodegenerative features might also be associated with cognitive impairments in DM1 ( Axford and Pearson, 2013 ; van der Plas et al, 2019 ; Labayru et al, 2020 ; Langbehn et al, 2021 ). A newly emerged opinion proposes that DM1 could be considered a progeroid disease (an early and accelerated aging process) ( Sansone et al, 2007 ; Modoni et al, 2008 ; Caso et al, 2014 ; Winblad et al, 2016 ; Gallais et al, 2017 ; Solovyeva et al, 2021 ), as typical symptoms related to aging, such as cognitive decline, occur in the early years.…”
Section: Developmental or Neurodegenerative?mentioning
confidence: 99%
“…In 2020, the first longitudinal study of structural brain involvement in pediatric and adult/late-onset DM1 shown that the brain volume loss over time in both groups was not significant compared with their healthy controls, thus supporting the probable occurrence of the neurodevelopmental process. However, these findings cannot completely rule out the existence of the neurodegenerative process, since patients were not yet in their 60’s at follow-up ( Labayru et al, 2020 ). In the future, additional studies with larger-sample and longitudinal observations are still needed to further clarify the feature of DM1 brain damages.…”
Section: Developmental or Neurodegenerative?mentioning
confidence: 99%
“…Diffusion tensor imaging studies have demonstrated widespread white matter lesions with reduced fractional anisotropy (FA) and increased mean diffusivity in patients with DM1 compared with controls (Cabada et al, 2017;Yoo et al, 2017;van Dorst et al, 2019). Widespread reduction of gray matter volume (including frontal, temporal, parietal, and occipital cortices, as well as deep gray matter structures and cerebellum) was found in patients with DM1 using the voxel-based morphometry method (Minnerop et al, 2011;Baldanzi et al, 2016;Zanigni et al, 2016;Hamilton et al, 2018;Park et al, 2018;Gliem et al, 2019;Labayru et al, 2019Labayru et al, , 2020Serra et al, 2020a;Cabada et al, 2021). Recent studies have investigated abnormalities in gray matter structural networks using graph theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%